Does harmonization reduce the impact of SPS measures on agricultural exports? An assessment from the Chilean fruit sector - Boza, Sofia; Muñoz, Jazmín; Cáceres, Javiera (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2023)
Non-tariff measures (NTMs) are relevant to agricultural trade policies, especially since trade negotiations have significantly decreased tariffs. Countries impose Sanitary and Phytosanitary Measures (SPS), a technical NTM, to protect human, animal, and plant health by regulating specific food quality and safety aspects. This article aims to assess the impact of SPS measures imposed by Chile’s main trading partners on agricultural trade, specifically on the value of fruit exports. It also seeks to determine the effects of harmonizing technical regulations between Chile and its partners. We estimated a gravity equation as a negative binomial regression model with Chilean fruit exports to main destination markets from 2010 to 2019 as the dependent variable. Our results confirm a negative impact of foreign SPS measures on Chilean fruit exports. However, that impact is mitigated if Chile has a harmonized SPS measure. Thus, we can conclude that harmonization reduces the negative effects of foreign SPS measures on exports. Our results suggest that trade agreements, which often contain a chapter on SPS, positively contribute to SPS harmonization and mitigate SPS’s negative impacts on trade flows. Highlights: Sanitary and Phytosanitary Measures (SPS), aim to protect human, animal, and plant health by regulating specific food quality and safety aspects. The impact of SPS on trade flows has been largely analyzed with heterogeneous results depending, among others, on their characteristics, as the level of harmonization. Harmonization reduced the negative effects of SPS measures on Chilean fruit exports flows. Trade negotiations might positively contribute to SPS harmonization, especially whether agreements have an SPS chapter that encourages coordination.